Shamba Shape Up series one development benefit and systemic impact - Africa Centre for Applied Research (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
Series One of SSU was broadcast on Citizen Television between March and June 2012. It is estimated that the series attracted an audience of around 3 million television viewers, based on the Kenya Advertising Research Foundation (KARF) industry recognized data for measuring the size and profile of television audiences. The Series One pre and post broadcast research among small holder farmers with access to television, produced evidence that the series had a positive direct impact on the knowledge, attitudes and behaviour of the small holder farmers who viewed at least some of the programmes. There was no indication of the value of this impact. In order to answer some of these questions a further research study was commissioned by the Africa Enterprise Challenge Fund (AECF) in June 2013. This report is largely based on the findings from that study.